PENINGKATAN KOMPETENSI GURU DALAM MEMBUAT MODUL AJAR DAN ASESMEN PADA KURIKULUM MERDEKA - Shahibah Yuliani; Nurul Istiqomah; Dian Alfia Purwandari; Fadia Rizky Agustin; Nova Scorviana H; Ridwan Guci; Muhammad Abdul Azis; Putri Cahyanti (LP2M STP Mataram, 2023)
Implementation of the Free Learning Curriculum is a challenge and part of efforts to improve the condition of education in Indonesia. Modifying the curriculum through the concept of independent learning is one of the efforts to produce quality human resources, but the facts on the ground that teachers are still unskilled do not understand lesson plans. Therefore, it is necessary to increase teacher competence through understanding lesson planning. In following the IPS learning assessment the teacher must fulfill two minimum requirements, namely meeting the existing criteria and learning activities in the teaching module according to the principles of learning and assessment. Research and community service activities will be carried out on Wednesday, 31 May 2023 from 08:00 to 15:30 WIB at Hang Tuah 1 Middle School Jakarta followed by Social Sciences Teachers at Private Middle Schools in the North Jakarta Region 2 with the aim of participants having an understanding of the independent curriculum and the practice of compiling learning assessments. This activity was carried out using interactive lecture methods, question and answer, video screenings, and practice of making teaching modules. Research and community service activities in the form of training in making teaching modules are very useful for developing teachers' abilities in making teaching modules. It is hoped that teachers can implement meaningful and differentiated teaching modules in the learning process by paying attention to student characteristics